Analisis Kelayakan Bahasa Buku Teks Bahasa Indonesia Kelas IX Kurikulum 2013 Terbitan Kemendikbud - Dicky Fahmi; Desi Arni Natalina Br. Siburian; Diah Ayu Lestari; Erni Tri Rezeki; Dearby Wandira Yulis; Muhammad Mukhlis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This study aims to describe the suitability/feasibility of the language of the 2013 Curriculum textbooks for grade IX students. The approach used in this research is the approachqualitative research with the type of content analysis (content analysis).Based on the textbook analysis that has been done, it can be drawnthe conclusion that Indonesian textbooks for class IX curriculumThe 2013 issue of the 2018 edition of the Ministry of Education and Culture meets the feasibility aspect Language with a percentage of 80% of the feasibility of using the language inside This textbook is included in the good category. Where is the Eligibility Language it has a section, it's in terms of straightforwardness of languagein textbooks, where is the simplicity in Indonesian textbooks The 2013 curriculum published by the 2018 edition of the Ministry of Education and Culture is good. Then from a communicative point of view, this section is also a language textbook Indonesia Curriculum 2013 published by the 2018 edition of the Ministry of Education and Culture has pretty good. The dialogue and interactive parts are also good, already includes all existing book assessments. And finally the suitability with the development of Indonesian textbook students The 2013 curriculum published by the 2018 edition of the Ministry of Education and Culture is good, a lotin the book there is a suitability for the development of students and very relevant.